Short‐process incudo‐stapedioplasty in congenital ear malformation - Ryotaro Omichi; Shin Kariya; Akiko Sugaya; Mizuo Ando (Laryngoscope Investigative Otolaryngology)
Abstract Objectives Although various stapedotomy and stapedectomy techniques exist, anchoring the piston can be challenging. We present a novel surgical approach for treating congenital stapes malformations with an atypical facial nerve trajectory. Methods This is a case of a 7‐year‐old boy presenting with bilateral conductive hearing loss. Prior attempts at tympanoplasty had proven unsuccessful in improving his hearing. Presurgical imaging studies revealed an unusual anatomical configuration, with the facial nerve positioned inferior to the oval window. This anatomical variation precluded the use of conventional prosthesis‐anchoring techniques typically employed in stapedotomies. Thus, we devised an innovative approach, opting to anchor the prosthesis to the short process of the incus. Results This novel technique circumvented the atypical course of the facial nerve, allowing for successful reconstruction of the ossicular chain. The patient demonstrated an acceptable improvement (30 dB gain) in hearing 1‐year post‐surgery, with no reported complications. Conclusion This case underscores the critical importance of adapting surgical techniques to address the unique anatomical challenges that may arise in the context of congenital ear malformations. It also highlights the potential of the short process of the incus as a viable alternative anchoring site for stapes prostheses, thereby improving the outcomes of such complex cases. This technique not only restored the patient's hearing but also contributed valuable insights into the management of similar cases, potentially improving the quality of life for individuals with rare and challenging anatomical variations. Level of evidence 5.